2012
DOI: 10.1002/cbdv.201100240
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Genetic Study of Ligularia duciformis and Related Species in Sichuan and Yunnan Provinces of China

Abstract: The chemical constituents of the root extracts and the evolutionarily neutral DNA base sequences were studied for 28 samples of Ligularia duciformis, L. kongkalingensis, and L. nelumbifolia collected in Sichuan and Yunnan Provinces of China. The samples could be classified into four chemotypes (1-4). Sesquiterpenoids having eremophilane and oplopane skeletons were isolated from two (Chemotype 1) and three (Chemotype 2) samples, respectively. Two new oplopane derivatives were isolated and their structures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…Hand .‐ Mazz . complex might have been acquired by hybridization . Thus, examination of the chemical consequences of hybridization should yield valuable information on the chemical diversity in Ligularia .…”
Section: Introductionmentioning
confidence: 99%
“…Hand .‐ Mazz . complex might have been acquired by hybridization . Thus, examination of the chemical consequences of hybridization should yield valuable information on the chemical diversity in Ligularia .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the 1D‐NMR signals suggested eight CH (including four O‐bearing methines groups), one CH 2 ( δ (H) 1.66 ( ddd , J = 11.0, 10.9, 3.2, H–C(8)), 2.16 ( ddd , J = 11.0, 11.0, 4.3, H–C(8)); δ (C) 33.8 (C(8))), and two Me groups, in which one ( δ (H) 1.21 ( s , H–C(13)); δ (C) 16.2 (C(13))) was attached to a tertiary C‐atom and the other ( δ (H) 1.43 ( d , J = 6.6, H–C(15)); δ (C) 16.4 (C(15))) to a secondary C‐atom. To accommodate an index of hydrogen insufficiency of eight, compound 1 was proposed as having a bicyclic sesquiterpene skeleton, with an epoxy group and an exocyclic C=C bond, in agreement with an oplopanoid sesquiterpene skeleton …”
Section: Resultsmentioning
confidence: 79%
“…The three species are taxonomically closely related to one another, growing in stream banks, forest understories, grasslands, and alpine meadows [7]. Recently we reported that the three species were indistinguishable, and presumably forming a complex; however, the plants were found to harbor four chemotypes; i.e., an eremophilane-producing type (type 1), an oplopane-producing type (type 2), a phenylpropenoid-producing type (type 3), and a type producing other compounds (type 4) [8]. Many phenylpropenoids [9], as well as sesquiterpenoids, such as eudesmanes, guaianes [10], oplopanes [11], and eremophilanes, including eremophilanolides [12], have been isolated from these species prior to our systematic search; however, no furanoeremophilane was isolated.…”
Section: Nelumbiforia (Bureau and Franch)mentioning
confidence: 99%